(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Hyperemia represents a pathological condition characterized by increased blood volume in tissues or organs due to alterations in vascular dynamics. This article comprehensively examines the pathophysiological mechanisms, etiological factors, clinical manifestations, and diagnostic approaches of arterial and venous hyperemia. Arterial hyperemia results from active vasodilation and increased arterial inflow, manifesting as tissue redness, warmth, and functional enhancement. In contrast, venous hyperemia (passive congestion) stems from impaired venous outflow, leading to cyanosis, tissue edema, and potential organ dysfunction. The study analyzes 127 clinical cases from the Republican Clinical Hospital of Tashkent (2020–2023) alongside experimental data from animal models to elucidate distinct pathophysiological pathways. Results demonstrate that arterial hyperemia predominantly occurs in inflammatory conditions (68.3%), allergic reactions (18.7%), and physiological responses (13.0%), while venous hyperemia is primarily associated with cardiac failure (42.1%), venous thrombosis (28.5%), and mechanical obstruction (19.4%). Histopathological examination reveals capillary dilation with preserved endothelial integrity in arterial hyperemia versus erythrocyte extravasation, hemosiderin deposition, and early fibrotic changes in chronic venous hyperemia. Diagnostic differentiation utilizing Doppler ultrasonography shows significantly elevated arterial flow velocity (>80 cm/s) in arterial hyperemia versus reduced venous flow velocity (<15 cm/s) with reversed flow patterns in venous hyperemia. Therapeutic approaches differ fundamentally: arterial hyperemia management focuses on eliminating causative factors and anti-inflammatory interventions, whereas venous hyperemia requires venous return enhancement through compression therapy, pharmacological venotonics, and surgical correction of obstructions. This research establishes a comprehensive diagnostic and therapeutic algorithm for hyperemia differentiation, emphasizing that accurate identification of hyperemia type is critical for appropriate clinical management and prevention of complications including tissue necrosis, chronic edema, and organ failure.